Thin surface layers of iron-based alloys deposited by TIG hardfacing - Sakiru, Adeleke; Md. Abdul, Maleque; Shahjahan, Mridha (Japanese Societies of Tribologists, 2015)

(untitled)
Hardfacing layers developed by tungsten inert gas (TIG) surface melting on commercial purity titanium placing with a mixture of Fe, C and Si powders under two different traverse speeds (1 mm/s and 2 mm/s) and energy input of 1080 J/mm in an argon gas environment were investigated in terms of surface condition, microstructure, hardness and wear of the processed tracks. The surface appearance of treated layers was found to be free from any obvious defect. The TIG hardfacing layer produced dendritic structure due to dissolution of preplaced powder in the Ti melt. A maximum microhardness value of 630 HV 0.5 kgf was found on the surface layer processed with lower speed which was 2.5 to 3.5 times higher than the base material. Ball-on-plate wear tests exhibited better performance of the hardfacing layer than the untreated CP-Ti which is attributed to the presence of carbides and silicides in the Ti melt.